Combination of nanoindentation and quantitative backscattered electron imaging revealed altered bone material properties associated with femoral neck fragility. - Fratzl-Zelman, N; Roschger, P; Gourrier, A; Weber, M; Misof, B; Loveridge, N; Reeve, J; Klaushofer, K; Fratzl, P (2009)
Osteoporotic fragility fractures were hypothesized to be related to changes in bone material properties and not solely to reduction in bone mass. We studied cortical bone from the superior and inferior sectors of whole femoral neck sections from five female osteoporotic hip fracture cases (74-92 years) and five nonfractured controls (75-88 years). The typical calcium content (Ca(Peak)) and the mineral particle thickness parameter (T) were mapped in large areas of the superior and inferior regions using quantitative backscattered electron imaging (qBEI) and scanning small-angle X-ray scattering, respectively. Additionally, indentation modulus (E) and hardness (H) (determined by nanoindentation) were compared at the local level to the mineral content (Ca(Ind)) at the indent positions (obtained from qBEI). Ca(Peak) (-2.2%, P = 0.002), Ca(Ind) (-1.8%, P = 0.048), E (-5.6%, P = 0.040), and H (-6.0%, P = 0.016) were significantly lower for the superior compared to the inferior region. Interestingly, Ca(Peak) as well as Ca(Ind) were also lower (-2.6%, P = 0.006, and -3.7%, P = 0.002, respectively) in fracture cases compared to controls, while E and H did not show any significant reduction. T values were in the normal range, independent of region (P = 0.181) or fracture status (P = 0.551). In conclusion, it appears that the observed femoral neck fragility is associated with a reduced mineral content, which was not accompanied by a reduction in stiffness and hardness of the bone material. This pilot study suggests that a stiffening process in the organic matrix component contributes to bone fragility independently of mineral content.